Automatic Wet Grinding System - V.Srimaheswaran,V.Sekhar, S.Zabiullah, Jawahar Eswar, R.Naveen, I.Bharath Kumar Reddy (International Journal of Advanced Science and Technology, 2020)
A wet grinder will sit down with either a tool for abrasive cutting of exhausting materials, or a food preparation appliance used particularly in Indian culinary art for grinding food grains to provide a paste or batter. A wet grinder for abrasive cutting uses fluid for lubrication or cooling, whereas one for food preparation uses water to mix with ground grain to provide batter. the present system of grinders is jam-packed with manual operation of grinding. The rice needs to soak manually and soaked rice ought to be born onto grinders manually. The grinding method needs little of water to be further whereas grinding, the care is taken till the rice is grinded fully and throw the system. Each step within the method needs human interference and data on grinding method. The most downside of the present system is that demand of manual operational. To facilitate a operating girls associate degreed for an aged people it‘s exhausting to try to to maintenance of wet grinder, so as to reduce the work load and time utilization it's complete by suggests that of entirely automatic wet grinder by fitting body of water and outlet valve and additionally appends timer devices. By doing this mechanically grinder will wash itself while not betting on the creature. In this paper timer, microcontroller, comparator device, water pump, water outlet valve square measure used. Principle of this paper is timer is employed to line the beginning and finish time of the wet grinder operate. Inorder to scale back human interference within the method we will up with a plan that will automatic operation of soaking and removing the waste water from soaked rice then to pour rice automatically and grind it with automatic water. Once grinding completed the system turns off grinder. This project sends standing of the system to user through GSM.